Lichenoid dysplasia is not a distinct pathological entity. (August 2021) - Farah, Camile S.; Fox, Simon; Shearston, Kate; Newman, Luke; Babic, Sharon; Vacher, Michael
Highlights: Oral Lichenoid dysplasia (OLD) is a controversial histological term with features of lichen planus (OLP) and epithelial dysplasia (OED) Few differentially expressed genes distinguish OLD from OLP, in comparison to OED. Bioinformatic profiling of immune cell populations in OLP and OLD were similar, and distinct from OED. Based on molecular data, OLD is not a distinct histopathological entity. Abstract: Objectives: Oral Lichenoid Dysplasia (OLD) is a controversial histological term applied to lesions that display features of oral lichen planus (OLP) and oral epithelial dysplasia (OED). In this study we investigated the molecular profiles of OLD, OLP and OED to determine whether OLD exists as a distinct pathological entity. Materials and Methods: Samples from patients presenting with lesions diagnosed histologically as OLP, OLD or OED underwent RNA sequencing followed by differential gene expression, functional enrichment and network analysis, sparse partial least squares discriminant analysis, and immune cell phenotypic estimation. Results: Unsupervised clustering demonstrated a group of genes with high expression in OLP and OLD, and low expression in OED, predominantly involved in inflammatory processes. Many genes were significantly differentially expressed between either OLD or OLP and OED, but few between OLD and OLP. Functional enrichment showed significant pathways and ontologies related to inflammatory signalling and immune response between OLD or OLP and OED. Broad commonality was found between OLP and OLD in upregulation of specific immune system pathways. Classifying models discriminated histologically diagnosed OLD from OED based upon molecular data alone. Bioinformatic profiling showed that immune cell populations in OLP and OLD were consistent, and distinct from OED. Conclusion: Molecular data shows that OLD is not a distinct pathological entity. Its transcriptomic and immunophenotypic profile is similar to OLP and distinct from OED. We recommend that oral lichenoid dysplasia not be used as a distinct pathological entity. Our data further supports exclusion of dysplasia in diagnosis of OLP.